NAVIGATIONAL SAFETY - Anastasia Fedorovna Shvetsova (International Journal of Advanced Studies, 2019)
This article is devoted to the origin of the concept of “navigation security zone”. The meaning of the term for modern theory and practice of navigation is described in detail, and the main stages of its development are described. Particular attention is paid to the interpretation of the concept by leading domestic and foreign scientists, on the basis of their views, advanced trends in the development of the theory of the navigation security zone are predicted.